2018
DOI: 10.21786/bbrc/11.4/24
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teachers professional identity: Role of teacher emotions in developing professional identity

Abstract: The purpose of this study is to develop an understanding of the connections between teacher's emotional development and professional identity. Twenty teachers in their beginning year of profession were interviewed to refl ect on emotional events and how these emotions help them in developing their professional identity. The research question for this study is; how do teachers' refl ections of emotional events contribute in the development of their professional identity? Findings of the research yielded a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In their coursework, diverse negative emotions triggered by external factors might undermine student-teachers' self-confidence, thus inhibit the development of their emerging identities and decrease their willingness to be teachers (Chen et al, 2020 ). Echoing previous research findings (Teng, 2017 ; Kaur, 2018 ), this study demonstrates the detrimental impact of negative emotions on professional identity construction. Multiple course-related factors including challenging tasks and assessment requirements leave student-teachers especially vulnerable to a wide array of negative emotions, which reduces their self-confidence, triggers self-doubt, and undermines their job motivation (Wolff and De Costa, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In their coursework, diverse negative emotions triggered by external factors might undermine student-teachers' self-confidence, thus inhibit the development of their emerging identities and decrease their willingness to be teachers (Chen et al, 2020 ). Echoing previous research findings (Teng, 2017 ; Kaur, 2018 ), this study demonstrates the detrimental impact of negative emotions on professional identity construction. Multiple course-related factors including challenging tasks and assessment requirements leave student-teachers especially vulnerable to a wide array of negative emotions, which reduces their self-confidence, triggers self-doubt, and undermines their job motivation (Wolff and De Costa, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…Oppositely, the positive emotions student-teachers experience during their coursework strengthen their emerging identities and increase their desire to be teachers. This study provides empirical evidence to the view that positive emotions provoked by student-teachers' sense of achievement and progress can raise their self-confidence (Bao et al, 2021 ) and boost their emerging identities (Yuan and Lee, 2016 ; Kaur, 2018 ; Chen et al, 2020 ). Faced with the difficult and demanding assignments to design lessons and conduct micro-teaching, the student-teachers invest considerable time and effort to grow from knowing nothing to someone who can complete the tasks independently.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These findings are consistent with previous studies [ 113 , 114 , 115 ] that when teachers present positive attitudes toward teaching and learning supervision, they tend to have positive emotions towards the teaching profession which in turn encourage them from performing effective and efficient teaching practices. Synonymously [ 116 ], found that school heads and teachers’ frequent discussions on teaching and learning practices improved novice teachers’ professional emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Identity means an explicit response to the question "who am I" [13]. The professional identity itself is evolving, which requests not only in a professional manner in job tasks but also in a personal way [14]. In addition, an individual has multiple identities so that the capability of maintaining the identity is critical.…”
Section: Introductionmentioning
confidence: 99%